Strategi Transformasi Taman Bacaan Masyarakat Berbasis Inklusi Sosial (Studi Kasus TBM Gada Membaca Ciamis) - Dzakia Durrotul Qolbi; Rully Khairul Anwar; Fitri Perdana; Elnovani Lusiana (Universitas Sebelas Maret Library, 2026)
This study aims to analyze the transformation strategy of the Community Reading Center (Taman Bacaan Masyarakat/TBM) Gada Membaca in Ciamis Regency based on a social inclusion approach. The research employed a qualitative case study design using interviews, observations, and documentation as data collection techniques. The study focuses on community needs analysis, the implementation of social inclusion-based transformation strategies, and the evaluation and sustainability challenges of TBM programs. The findings indicate that community needs extend beyond access to reading materials to include alternative learning spaces, literacy assistance, and inclusive social interaction spaces. The implementation of the transformation strategy is carried out in a participatory manner involving managers, volunteers, village government, and the local community, enabling programs to be tailored to local needs. However, program sustainability remains challenged by limited human resources, modest facilities, and dependence on volunteers. This study highlights that TBM Gada Membaca has transformed into a community-based learning space grounded in social inclusion, but requires strengthened management and sustained support to ensure long-term effectiveness